Nitrogen Removal in the Anammox Biofilm Reactor using Palm Fiber as Carrier in Tropical Temperature Operation - Zulkarnaini Zulkarnaini; Ansiha Nur; Wina Ermaliza (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2019)
Anaerobic ammonium oxidation (anammox) is the process of converting ammonium directly into nitrogen gas with nitrite as an electron acceptor under anaerobic conditions. This process is more effective than conventional nitrification-denitrification but is very dependent on several parameters, one of which is temperature. The optimum temperature range for the growth of anammox bacteria is 30-400C. The purpose of this research was to determine the efficiency of nitrogen removal by anammox process using palm fibers in the Up-Flow Anaerobic Sludge Blanket (UASB) reactor in the tropical temperature. The experiment was conducted at a laboratory scale with a variation of Hydraulic Retention Time (HRT) 24 h and 12 h using artificial wastewater. The reactor was inoculated with anammox granule genus Candidatus Brocadia. The concentration of ammonium, nitrite, and nitrate in the influent and effluent were measured using a UV-Vis spectrophotometer based on standard method. Based on the experiment, the ratio ΔNH4+-N:ΔNO2--N and ΔNO3--N:ΔNH4+-N similar with stoichiometric of anammox. The maximum Nitrogen removal performance (NRT) achieved 0.11 kg-N/m3.d at Nitrogen Loading Rate (NLR) 0.14 kg-N/m3.d and 0.20 kg-N/m3.d at NLR 0.29 kg-N/m3.d. The removal efficiency for Ammonium Conversion Efficiency (ACE) and Nitrogen Removal Efficiency (NRE) in HRT 24 h were 79% and 76%, respectively while decreased in HRT 12 h were 72% and 69%, respectively. Anammox process can be applied in the tropical temperature at a laboratory scale using a UASB reactor with palm fiber as the carrier.